Opiates control ACTH through a noradrenergic mechanism. - Grossman, A; Besser, G (1982)
The administration of 16 mg of naloxone to six normal male subjects produced a significant rise in plasma cortisol. Pre-treatment with the noradrenergic α1-antagonist, thymoxamine 0.2 mg/kg, blocked this rise. It is suggested that opiate inhibition of the pituitary-adrenal axis is mediated via a noradrenergic pathway.